Conference management system (template design) / Norsyahida Sulaiman - Sulaiman, Norsyahida (2010)
A conferences objective is to give an opportunity to authors to present their papers. The conferences have their own committee members to organize and advertise it. However to reduce the time consuming, online system would be the best solution. For those who are not IT savvy we provide this web based conference management system to help them. This Conference Management System consist website templates and various item needed such as date, theme and payment regarding the conference that going to be held. This web based conference management system will give the committee who have the authority to apply conference websites template using this system. This system offer few layouts of conference websites where the user will have opportunity to decide or choose the best layout that suit the conference theme. This system also support for conference website template, where difference conference can use different website design based on the user requirement in order to meet the conference theme and objectives. This system is preferable on making a design template website. This system will use PHP as platform in order to develop this system.